RANCANG BANGUN SISTEM INFORMASI ONLINE PENERIMAAN SISWA (STUDI KASUS SMP AL-YAUMA JAKARTA) - Maruloh Maruloh; Mochamad Nandi Susila; Muhammad Darussalam (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Abstract Data processing new students at SMP AL-YAUMA Jakarta still dome conventionally, prospective applicants should come directly to the registration and fill the registration form and then the data registration was recorded on the books and preparing report also using conventional recap so frequent occurrence as well as the loss of archives time that is used to creat reports require a very long time. This research aims to solve these problems, by designing a new student admission information system based online so that prospective students do not have to come directly to the registration site and make it easier for officers to make reports. The research method that researchers use in this research is collecting reference sources with bibliography, interviews, and observation, and software development methodology with waterfall methodology. For testing the system used blackbox testing system. With this research is expected to help prospective new students and admissions officers new in facilitating the course of existing system.